Clinical pharmacy - at what stage are we in Poland? - Adrian Bryla; Kamila Urbańczyk; Anna Stachowiak; Magdalena Burkacka; Michał Steczko; Anna Wiela-Hojeńska (Polish Pharmaceutical Society, 2020)
The functioning of health care centers is highly dependent on the quality of cooperation between medical staff - doctors, nurses, but also pharmacists. Pharmaceutical knowledge about medicines, combined with daily practice and supervision of the pharmacotherapy used, can bring a number of benefits, primarily increasing effectiveness and safety of treatment, as well as reducing the cost of treatment. Despite numerous difficulties, in some hospitals in Poland pharmacists undertake various types of clinical activities by directly joining the work of a hospital ward or remote monitoring of patient's pharmacotherapy using electronic systems. It should be emphasized that these are often tasks carried out outside the basic dimension of working time. The initiative taken in 2017 by the Director of the Provincial Specialist Hospital in Wroclaw, Research and Development Center, deserves a mention. Pharmacist (during the specialization in clinical pharmacy) was fully engaged in the work of hospital wards focusing first in the Department of Vascular Surgery, and then also General Surgery. Her daily duties include participation in medical celebrations, conducting medical history with newly admitted patients, optimization of pharmacotherapy, consultation with the medical and nursing team, control of orders and results of laboratory tests, giving advice to staff and educating patients in correct use of medicines. This kind of multidisciplinary cooperation has become a standard of care, which has been approved by the accreditation committee of the Center for Quality Monitoring in Health Care. In Poland, clinical pharmacy is constantly developing and gaining importance every year, but as of today, there are still no clear law regulations. Will the draft Act On The Pharmacy Profession adopted by the Council of Ministers introduce regulations and clearly define the place of a clinical pharmacist in the healthcare system? Undoubtedly, it would be a basic step to the further development of clinical pharmacy services.